Sweet and blessed country: the Christian hope for heaven - Saward, John (Oxford University Press, 2005)
Sweet and Blessed Country is a theology of Heaven based upon a painting of Heaven. John Saward writes with an academic rigour that will interest scholars, but also with a simplicity that will speak to a wider readership. Here is a book for every Christian, indeed for every human being who yearns for a life and a happiness that will be unending